Positive psychology and employee adaptive performance: systematic literature review - Tang, Guihong; Abu Bakar, Raida; Omar, Safiah (Frontiers in Psychology, 2024)
Adaptive performance will increasingly be confronted with new insights as society today changes constantly. This raises questions as to what factors will impact employee’s adaptive performance and what is their inner psychological mechanism. The terms of positive psychology and adaptive performance are important concepts in the domain of organizational behavior and human resource development areas. The literature, however, lacks a systematic review of it. Our research seeks to explore the inherence of employee adaptive performance via the prism of positive psychology, including Psychological Capital and PERMA (Positive Emotions, Engagement, Relationships, Meaning and Accomplishment). We selected 27 papers out of 382, which were generated from Web of Science and Scopus databases associated the keywords of the two concepts, and used the 2020 PRISMA flow program for the paper screening. By analyzing the underpin theories, the causation, and the measurement, we discovered that there is a complex and nuanced relationship between positive psychology and adaptive performance, and most of the research to date suggests that positive psychology components improve employee adaptive performance. This study maps the current knowledge at the nexus of positive psychology and adaptive performance to identify existing gaps and potential for further investigation.